Efficacy and safety of PD-1 inhibitors plus chemotherapy with or without endostatin for stage IV lung squamous cancer: a retrospective study - Lv, Chengliu; Wu, Yahua; Gu, Weiwei; Du, Bin; Yao, Na; Zhu, Yingjiao; Zheng, Jianping; Hong, Yaping; Lai, Jinhuo (Frontiers in Immunology, 2024)
Backgroud: The study aimed to analyze the efficacy and safety of PD-1 inhibitors plus chemotherapy with or without endostatin for stage IV lung squamous cell carcinoma (LUSC). METHODS: A total of 219 patients with stage IV LUSC were included. 120 received PD-1 inhibitors plus chemotherapy with or without endostatin (IC±A), of which 39 received endostatin (IC+A) and 81 did not receive endostatin (IC-A). 99 received chemotherapy with or without endostatin (C±A). Endpoints included overall survival (OS), progression-free survival (PFS), adverse events (AEs), and immune-related adverse events (irAEs). RESULTS: The median PFS in the IC±A group versus the C±A group was 8 and 4 months (P < 0.001), and the median OS was 17 and 9 months (P < 0.001). There was no significant difference in any grade AEs between the IC±A and C±A groups (P > 0.05). The median PFS in the IC+A group versus the IC-A group was 11 and 7 months (P = 0.024), and the median OS was 34 and 15 months (P = 0.01). There was no significant difference between the IC+A group and the IC-A group for all grade AEs and irAEs (P > 0.05). The subgroup analysis showed that patients with LIPI = 0 had significant OS and PFS benefits in IC+A group, while for patients with LIPI = 1-2, there was no significant difference in OS and PFS benefits between the IC+A group and IC-A group . CONCLUSIONS: PD-1 inhibitors plus chemotherapy with endostatin might be first-line treatment for patients with stage IV LUSC.